Spatial Analysis of The Number of Poor Population in East Java Province In 2023 - Rajagukguk, Marlon Brando (Educational Studies and Research Journal, 2024)
Poverty has many important influences in a country because of the broad and complex impact it has on individuals, society, and the economy as a whole. The use of spatial analysis techniques in the context of poverty is important to understand the spatial distribution and factors related to economic inequality in the region. The aim of this research is to descriptively analyze the regional interrelationships of the Open Unemployment Rate (TPT), Human Development Index (HDI) and Number of Poor People variables, as well as analyzing inferentially to determine variables that significantly influence the Number of Poor People. The spatial analysis method used in This research involves descriptive and analysis methods Ordinary Least Squares (OLS). From this research it is concluded that the variables TPT, HDI and Number of Poor Population are related between regions because they have a Moran's I Index > 0. In the OLS Analysis it can be concluded that the variable Number of Poor Population can be influenced statistically significantly by the variables Open Unemployment Rate and Human Development Index Abstract is a summary of an article written in one paragraph. Maximum 200 words. The abstract must contain background and objectives, methods, results and conclusions.